Restorative Justice Terhadap Tindak Pidana Penggelapan Pajak Dibawah 500 Juta Dalam Prespektif Keadilan - Situmorang, Kristensen Marihot; Lyanthi, Merline Eva (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Tax evasion offenses involving amounts under IDR 500 million often present a dilemma between criminal law enforcement and the efficiency of recovering state losses. The conventional retributive justice system frequently fails to provide optimal outcomes in terms of legal certainty and financial recovery. This study aims to explore the potential implementation of restorative justice as an alternative approach for resolving minor tax evasion cases and to evaluate how well this approach aligns with the principles of substantive justice. The research employs a normative and empirical legal method, analyzing existing regulations and drawing comparisons with practices in other jurisdictions. The findings indicate that restorative justice offers a more equitable and efficient solution, provided that strict case selection criteria are applied, offenders are willing to take responsibility, and a transparent oversight mechanism is in place. It concludes that adopting restorative justice in low-scale tax evasion cases may help restore state losses without compromising the values of justice and legal certainty.